Eosinophilic pancreatitis versus pancreatitis associated with eosinophilic gastroenteritis - a systematic review regarding clinical features and diagnosis - Pinte Larisa; Băicuș Cristian (Sciendo, 2019)
Background. Over the past years, eosinophil infiltration involving the gastrointestinal tract and pancreas leading to eosinophilic pancreatitis, eosinophilic gastroenteritis and hypereosinophilic syndrome has been reported in the literature.